Stabilizing Buried Interface via Synergistic Effect of Fluorine and Sulfonyl Functional Groups Toward Efficient and Stable Perovskite Solar Cells - Gong, Cheng; Zhang, Cong; Zhuang, Qixin; Li, Haiyun; Yang, Hua; Chen, Jiangzhao; Zang, Zhigang (Nano-micro letters, 2023)
Highlights An effective buried interface stabilization strategy based on synergistic effect of fluorine and sulfonyl functional groups is proposed. The correlations between molecular structures, defect passivation, interfacial energy band alignment, perovskite crystallization and device performance are established. The device with KFSI achieves an impressive efficiency of 24.17%. The interfacial defects and energy barrier are main reasons for interfacial nonradiative recombination. In addition, poor perovskite crystallization and incomplete conversion of PbI 2 to perovskite restrict further enhancement of the photovoltaic performance of the devices using sequential deposition. Herein, a buried interface stabilization strategy that relies on the synergy of fluorine (F) and sulfonyl (S=O) functional groups is proposed. A series of potassium salts containing halide and non-halogen anions are employed to modify SnO 2 /perovskite buried interface. Multiple chemical bonds including hydrogen bond, coordination bond and ionic bond are realized, which strengthens interfacial contact and defect passivation effect. The chemical interaction between modification molecules and perovskite along with SnO 2 heightens incessantly as the number of S=O and F augments. The chemical interaction strength between modifiers and perovskite as well as SnO 2 gradually increases with the increase in the number of S=O and F. The defect passivation effect is positively correlated with the chemical interaction strength. The crystallization kinetics is regulated through the compromise between chemical interaction strength and wettability of substrates. Compared with Cl − , all non-halogen anions perform better in crystallization optimization, energy band regulation and defect passivation. The device with potassium bis (fluorosulfonyl) imide achieves a tempting efficiency of 24.17%.